A case of acute radiation enteritis: recommendation to perform colonoscopy together with histopathological examination - Ikezaki, Osamu; Okabe, Naota; Sato, Taro; Tonari, Ayako; Hayashida, Mari; Mori, Hideaki; Mochizuki, Makoto; Saito, Daisuke; Shibahara, Junji; Tokunaga, Kengo; Hisamatsu, Tadakazu; Sakuraba, Akihito; et al. (JOURNAL OF THE KYORIN MEDICAL SOCIETY, 2018)
Acute radiation enteritis is often self-limiting and reversible as long as radiotherapy ceases within a short period. Colonoscopy is thus rarely performed and the endoscopic findings have not been fully investigated. We encountered a case of acute radiation enteritis in which colonoscopy was performed. The patient was a 68-year-old man with prostatic cancer under hormone therapy. Back pain due to metastasis to the pelvic area developed, and radiotherapy was adopted. However, watery diarrhea began 4 days after the initiation of radiotherapy. Colonoscopy revealed mucosal erythema, edema, and epithelial friability with mucus adhesion in the sigmoid colon. Biopsied specimens showed shedding of superficial epithelium, atrophy of crypts, and infiltration of inflammatory cells into the lamina propria. On the basis of endoscopic and histopathological findings as well as the clinical pictures, acute radiation enteritis was diagnosed. Symptoms gradually improved after radiotherapy was suspended. Follow-up colonoscopy confirmed recovery to normal-appearing intestinal mucosa. When symptoms suggestive of colitis develop shortly after initiating radiotherapy, colonoscopy together with histopathological examination should be actively performed to achieve definitive diagnosis of acute radiation enteritis.